(untitled) (Heritage, 2020)
Yugoslavia was a complex political structure made up of six republics and two autonomous provinces, both within Serbia. In early 1989, the situation in Kosovo was complex. In the middle of March 1989, violent demonstrations began in the cities of the autonomous province of Kosovo. The participants in the demonstrations were Kosovo Albanians. The situation in Kosovo wasdiscussed at the sessions of the Presidency of the SFRY. The paper presents the conclusions and measures taken by the Presidency of the SFRY to normalize the situation in Kosovo. When taking measures to eliminate Albanian nationalism and separatism, the Presidency of the SFRY was guided by the Constitution (1974), but also by considering how the measures would affect internal political relations in Yugoslavia and the international position